Dumb beasts and dead philosophers humanity and the humane in ancient philosophy and literature - Osborne, Catherine (Oxford : Clarendon, 2007)
This unusual philosophy book asks the reader to reconsider the received view that animal rights have no place in ancient thought. Catherine Osborne argues that by reflecting on the work of the ancient philosophers and poets, we can see when and how we lost touch with the natural intelligence of dumb animals.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Animal welfare -- Philosophy -- History; Philosophy, Ancient; Animals in literature; Literature, Ancient -- History and criticism; Animals and civilization